(untitled) (AUN INTERNATIONAL CONFERENCE, 2025)
Artificial Reproductive Technologies are medical procedures where sperm, egg or embryo are manipulated to achieve healthy and successful pregnancy. Infertility is a significant reproductive health issue in Nigeria, leading to serious social and economic effects. In this study, the Nigerian public awareness, perceptions, and attitudes toward assisted reproductive technologies (ART) was investigated using a structured questionnaire administered online to 414 Nigerians from the six geopolitical zones. The results revealed that 65.7% of respondents had positive views of ART, and 83.3% supported broader availability. Awareness was greater among females, Christians, and those with higher incomes. Logistic regression showed that sex, education, employment, and income were important predictors for acceptance of ART. Cultural and religious beliefs influenced the views of more than half of the respondents, while high costs and limited access were significant barriers. The findings emphasize the need for targeted education, culturally respectful engagement, regulation, and affordability measures to improve ART acceptance in Nigeria.